Geomagnetic Storm Impacts on Communication, Navigation, Surveillance, and Air Traffic Management (CNS/ATM) (London Journal of Engineering Research, 2022)
On 17 March, and 23 June 2015 secondary Air Traffic Control (ATC) radar was strongly disturbed in Cairo Air Navigation Center (CANC) with deterioration and interruptions of communications (Di) at Cairo international airport the disturbances occurred when the radar antennas were pointing at the Sun. In this paper, we are studying the impacts of geomagnetic storms on Communication, Navigation, Surveillance, and Air Traffic Management (CNS/ATM) by researching and analyzing the number of hours in a geomagnetic storm per year. According to Dst (
Keywords: geomagnetic storms / sunspot number (ssn)/ communications; navigation; surveillance (cns) and satellite solar outage